Gender-Based Violence Among Pharmacists Working in Healthcare Hospitals: A Cross-Sectional Study - Bista, Binamra; Karki, Sandip; Gurmaita, Raman Kumar (Med Phoenix, 2024)
Introduction: Gender-based violence (GBV) is a pervasive issue affecting healthcare professionals globally, including pharmacists. In Nepal, pharmacists working in tertiary healthcare settings may face unique challenges related to GBV. This study aims to explore the prevalence and impact of GBV among registered pharmacists in these settings. Materials and Methods: A cross-sectional study was conducted among 105 randomly selected registered pharmacists working in tertiary healthcare hospitals in Nepal. Data were collected using a structured questionnaire that assessed experiences of GBV, workplace environment, and support systems. The study employed descriptive statistics and chi-square tests for data analysis using SPSS version 20.0. Results: The study found that 35.23% of pharmacists reported experiencing some form of GBV in the workplace. Verbal abuse was the most common form (59.45%), followed by psychological (21.62%) and physical violence (10.81%). Female pharmacists were significantly more likely to experience GBV than their male counterparts (p<0.01). Only 27.02% of those affected reported incidents to their supervisors, citing fear of retaliation and lack of institutional support as primary barriers. Conclusion: Addressing GBV in healthcare settings is crucial to ensuring a safe and equitable work environment for pharmacists. Efforts should focus on enhancing awareness, strengthening institutional policies, and providing comprehensive support to victims.